Carbonate sedimentology of coral reefs in Sumba Island, Indonesia - Ramos, Cedrick (My University, 2022)
The Island of Sumba, Indonesia, comprises several reef terraces formed by changing global sea levels and episodic tectonic activity. Volcanic-derived sediment has been found to have been incorporated into reef fabrics without impacting coral growth. The uninterrupted reef growth shows a conflicting theory that coral reefs do not survive under significant clastic input. Continuous reef growth has been documented in this region known as the Coral Triangle. However, it is unclear whether intervals of increased clastic content affect coral growth strategies or whether the immature nature of the volcaniclastic sediment (larger and angular grain) explains why clastic input does not choke corals. This study employs various thin sections from fossil reefs (late-Pleistocene) to document and characterize the sediment’s size and circularity, which is a measure of sediment maturity. The study involves imaging analysis by taking images of each thin section. The thin sections have all been stained with Alizarin red, a stain that only turns calcite or aragonite grains a shade of red, and all other minerals remain unstained. Then, the images were colour indexed to black and white, with clastic grain appearing as white. The images underwent thresholding to isolate the white grains to measure their circularity and sizes. It was found that the grains of the sediments are sand size and angular, which means that the grains only have some transported involved, but they did not deposit far away from their source. A range of grain sizes in these sections have revealed that some of the grains detected are small enough to enter corallites and pores in the coral skeleton, while others are much larger and would not impact the coral growth.
Presented on April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta and May 5-6, 2022 at the Undergraduate Research in Science Conference of Alberta held at MacEwan University in Edmonton, Alberta.
Keywords: sedimentology; coral reefs and islands; Sumba Island (Indonesia)